Space, society and culture: housing and local level politics in a section of Alexandra township, 1991-1992 - Lucas, Justine, Clare (My University, 1995)
This thesis presents an analysis of the relationship between social processes, cognitive understandings and the organisation of space, as this pertains to local-level politics in a section of Alexandra township, South Africa, during 1991 and 1992. The context of the thesis is the attempts by the Alexandra Civic Organisation and the Alexandra branch of the African National Congress to elicit support from people living in formal and inform~i housing during a period of intense violence. The focus of the ethnographylis on local-level civic structures and political leadership, which in some ways support and in others contradict the aims and objectives of these two organisations. The reason for this internal political diversity is that local-level politics is embedded within social maps - cognitive orderings of space that represent patterns of social relations and structures of power. This points to the main theoretical focus of the thesis: the interrelationship of space, culture and society in an urban context. Urbanism is conventionally defined in sociological and geographical terms as the articulation between social process and urban spatial form. The thesis shows how anthropology can make a contribution to this field of study by incorporating a concern with culture. The mutually constitutive relationship of urban space, culture and society presents a way of looking at urbanism that does not depend on a rural-urban dichotomy; a social. and cultural dualism which is conventionally fitted into a modernist narrative of urbanisation. The ethnography in the thesis demonstrates the inapplicability of this narrative, and the categories of rural tradition and urban modernity which it implies. Keywords: anthropology, urbanism, urbanisation, rural-urban dichotomy, space, Alexandra, politics, civic organisation, informal housing.
A thesis submitted to the Faculty of Arts, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Arts, 1995
Keywords: Housing policy -- South Africa; Alexandra (Johannesburg, South Africa) -- Social conditions; Squatter settlements -- South Africa -- Johannesburg